Diversity of organ-specific plant transcriptomes - Michał Rurek (Acta Biochimica Polonica)
Plant transcriptomes comprise nuclear and organellar (mitochondrial and plastid) transcripts expressed by nuclear and organellar genomes, respectively. They are spatiotemporally shaped during development. The aim of this review was to summarize the most relevant transcriptomic responses in various plant organs and tissues in the developmental context. The dynamicity of organ- or tissue-specific transcriptomic responses was discussed based on the complexity and diversity of the recently characterized plant genomes and transcriptomes. Data were taken from high-throughput studies on numerous species, including model, crop and medicinal plant species. Vascular element transcriptomes as well as the root, leaf, flower and seed transcriptomes were exhaustively characterized. Transcriptomic alterations within various tissue and organ-specific transcriptomes employed various gene classes depending on the species, a given organ/tissue and the developmental stage. The specificity of organ-specific transcriptomes related to the over-representation of certain gene families and a plethora of transcription factors was focused. In addition, transcriptomes of medicinal plant species were characterized. The perspectives of medicinal plant species to synthesize valuable secondary metabolites (including quinones, carotenoids, phytoestrogens, terpenoids, steroids, flavonoids, phenolic derivatives, polysaccharides, glycosides, anthocyanins and macrocyclic peptides) were described based on organ transcriptomic patterns. Future research should be broadened by investigation of transcriptomes from field grown plants. Also, the potential of biomedical plants should be better revealed by genetic engineering and genome editing in further biotechnological applications.